Real-world national trends and influencing factors preference of non-vitamin K antagonist oral anticoagulants in China - Zhu, Shaojing; Li, Mengjie; Wang, Lujun; Hou, Lu; Li, Dandan; Liu, Jiuhong; Lu, Yanxia (Frontiers in Medicine, 2023)
Backgrounds: Non-vitamin K antagonist oral anticoagulants (NOACs) have been recommended as the first choice over warfarin for non-valvular atrial fibrillation (AF).However, there is limited data about their usage in mainland China.: Prescriptions of patients diagnosed with AF and containing OACs were extracted from Hospital Prescription Cooperation Project from January 2016 to March 2021. The primary outcome was the changing percentage of different OACs. The secondary outcomes were frequencies as well as factors with the choice of different OACs and dosage of NOACs. Univariate and Multivariate logistic regressions were conducted to explore possible factors. All statistical analyses were performed using SAS software (Version 9.4). Results: Among the 220,083 distinct prescriptions diagnosed with AF and prescribed with OACs, the percentage of NOACs increased over years, exceeding warfarin in 2018. Until March 2021, 83.53% of included patients were prescribed with NOACs.Rivaroxaban (62.25%) and dabigatran (37.65%) were the most commonly prescribed NOACs. Low dosage was common for NOACs (44.54%), this was mainly driven by rivaroxaban, 67.98% of which were low dosage.Multivariate logistic regression indicated that several factors were positively associated with the preference of low